(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
Employee work-life balance has been a subject of debate overtime; and there is a need to allow employee balance work with other personal goals; hence the introduction of remote work. Remote work as a concept is still alien to the global south (developing countries) like Nigeria unlike the global North (developed countries) where it is more pronounced. It is on this note that this study examined remote work and work-life balance among selected employees of Polaris Bank Nigeria. The study was anchored on the boundary theory and spill-over theory. Primary data was obtained from 150 respondents using a structured questionnaire. Findings evinced clearly that remote work has significant effect on work-life balance at (R2= 0.730, p-value